Nurse-facilitated preexposure prophylaxis delivery for adolescent girls and young women seeking contraception at retail pharmacies in Kisumu, Kenya. (15th March 2023) - Pintye, Jillian; Odoyo, Josephine; Nyerere, Bernard; Achieng, Pauline; Araka, Evelyne; Omondi, Christine; Ortblad, Katrina F.; Mugambi, Melissa L.; Baeten, Jared M.; Bukusi, Elizabeth A.
Abstract : Objective: We evaluated preexposure prophylaxis (PrEP) uptake, initiation, and continuation within a nurse-facilitated pharmacy-based delivery model for Kenyan adolescent girls and young women (AGYW) seeking contraception at retail pharmacies. Methods: From October 2020 to March 2021, PrEP-trained nurses were stationed at three retail pharmacies in Kisumu, Kenya. AGYW (aged 15–24 years) purchasing contraception (emergency contraception, oral contraceptive pills, injectables, implants, condoms) were counseled on PrEP, completed HIV testing, and offered a free 1-month supply of PrEP pills per national guidelines by nurses under supervision of a remote physician. We evaluated uptake among all AGYW offered PrEP. At 30 days after uptake, we evaluated PrEP use initiation and plans for continuation. Results: We enrolled 235 AGYW clients who were HIV-negative and purchasing contraception at pharmacies. Emergency contraception was the most frequently purchased contraceptive (35%). Median age was 22 years (IQR 19–23), 44% were currently in school, and 33% currently had multiple sexual partners. One-fourth (24%) exchanged sex for money or favors and 14% had sex while intoxicated in the prior 6 months. Overall, PrEP uptake was 85%; at 1 month, 82% had initiated PrEP use and 68% planned to continue use. Among those initiating PrEP, 69% were willing to pay for PrEP at retail pharmacies (median KES 150, IQR 100–200) even if available for free at public sector facilities. Conclusion: In this evaluation of nurse-facilitated PrEP delivery at pharmacies in Kenya, a substantial proportion of AGYW who purchased contraception subsequently initiated PrEP, planned to continue use, and were willing to pay for PrEP.